A quantitative assessment of the trade openness – economic growth nexus in India. Issue 3 (7th September 2015) - S.K. Shanthi, Prof Sanjoy Sircar, Dr K. Srinivasa Reddy, Dr; Pradhan, Rudra P.; Arvin, Mak B.; Norman, Neville R.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is motivated by research-based assertions that: the causes of economic growth in countries like India are not well understood; they are not elucidated by using simple bivariate relationships between economic growth and other variables, taken one at a time; and dynamic linkages between growth, trade openness and financial sector depth are required for any comprehensive treatment of this inquiry. Design/methodology/approach – This paper investigates the pivotal role of financial depth (defined as the relative importance in the economy of the banking sector or the stock market) and whether it bears any evidential relationship to trade openness and economic growth during the era of Indian post-globalization since 1990. Two key objectives are to uncover whether there is a long-run relationship between the variables and whether they can be said to cause one another. Autoregressive distributive lag (ARDL) bounds testing procedures and vector autoregressive error correction model (VECM) approaches were used to derive the results. Findings – This paper affirms that the variables are indeed formally cointegrated. It was also found that trade openness, economic growth and financial sector depth Granger-cause each other. Practical implications – This paper demonstrates that greater trade openness can predictably accelerate India's economic growth. If policymakers wish to maintain sustainable economic growth in India, they can do so by encouraging both freer trade and financial market development in the long run. Originality/value – No investigation of this type and sophistication has hitherto been performed for India. The methods developed for this study can also be applied to any of the vast range of countries for which dynamic growth-openness-financial depth interactions have not already been investigated.